Introducing the “Mathematical Modelling and Numerical Simulation of Combustion and Fire” Section of the Journal Fire - Ali Cemal Benim (Fire, 2022)
It is my immense pleasure to assume the role of Editor-in-Chief for the “Mathematical Modelling and Numerical Simulation of Combustion and Fire” Section of Fire, which is intended to take a leading role in the dissemination of high-quality research in this area [...]